Circulating tumor cell-derived preclinical models: current status and future perspectives - Kahounová, Zuzana; Pícková, Markéta; Drápela, Stanislav; Bouchal, Jan; Szczyrbová, Eva; Navrátil, Jiří; Souček, Karel (Cell death & disease, 2023)
Despite the advancements made in the diagnosis and treatment of cancer, the stages associated with metastasis remain largely incurable and represent the primary cause of cancer-related deaths. The dissemination of cancer is facilitated by circulating tumor cells (CTCs), which originate from the primary tumor or metastatic sites and enter the bloodstream, subsequently spreading to distant parts of the body. CTCs have garnered significant attention in research due to their accessibility in peripheral blood, despite their low abundance. They are being extensively studied to gain a deeper understanding of the mechanisms underlying cancer dissemination and to identify effective therapeutic strategies for advanced stages of the disease. Therefore, substantial efforts have been directed towards establishing and characterizing relevant experimental models derived from CTCs, aiming to provide relevant tools for research. In this review, we provide an overview of recent progress in the establishment of preclinical CTC-derived models, such as CTC-derived xenografts (CDX) and cell cultures, which show promise for the study of CTCs. We discuss the advantages and limitations of these models and conclude by summarizing the potential future use of CTCs and CTC-derived models in cancer treatment decisions and their utility as precision medicine tools.
Keywords: Heterografts; individualizovaná medicína; lidé; buněčné kultury; nádorové cirkulující buňky; Cell Culture Techniques; Precision Medicine; heterografty; Neoplastic Cells, Circulating; transplantace heterologní; Transplantation, Heterologous; Humans